2021
DOI: 10.1101/2021.02.19.431962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single cell atlas of human teeth

Abstract: Teeth exert fundamental functions related to mastication and speech. Despite their great biomedical importance, an overall picture of their cellular and molecular composition is still missing. In this study, we have mapped the transcriptional landscape of the various cell populations that compose human teeth at single-cell resolution, and we analyzed in deeper detail their stem cell populations and their microenvironment. Our study identified great cellular heterogeneity in the dental pulp and the periodontium… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 66 publications
0
48
0
Order By: Relevance
“…Recently, we performed a thorough single cell RNA sequencing analysis of the human dental pulp and periodontium 37 . We here interrogated this dataset to determine the expression of NOTCH receptors and ligands in dental pulp and periodontal MSCs (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we performed a thorough single cell RNA sequencing analysis of the human dental pulp and periodontium 37 . We here interrogated this dataset to determine the expression of NOTCH receptors and ligands in dental pulp and periodontal MSCs (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Notch3 ‐expressing MSCs are essentially predisposed to differentiate into hard tissue forming cells, contributing to the remodeling and healing of the injured pulp‐dentin complex. In our recent work, we showed that the similarity of MSCs in the dental pulp and the periodontium is counteracted by a great divergence in the composition of their niches 37 . However, previous studies from other laboratories had identified dental pulp and periodontal MSCs as divergent cell populations with distinctive properties 51‐53 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations